Service, Ethnography, and the “Leap of Faith”: A Spiritan Catholic Perspective on Service Learning - Roberts, Kathleen Glenister (Catholic Education: A Journal of Inquiry and Practice, 2008)
This article considers the state of service and experiential learning initiatives in higher education, especially in Catholic universities. Concluding that the Catholic mission of service, education, moral values, world concerns, and ecumenism can be integrated into student experience, the essay offers a model of service ethnography. Service ethnography is a research method wherein ethnographers undertake service with the intercultural community as a central component of their learning. The model is explored via a case study, demonstrating the experiences of students at a Catholic university and uses their reflections to describe a new vision of ethnography as a “leap of faith.”